Epidemiology, characteristics, and survival of post‐colonoscopy colorectal cancer in Asia: A population‐based study. Issue 9 (15th May 2019) - Cheung, Ka Shing; Chen, Lijia; Seto, Wai Kay; Leung, Wai K
Abstract: Background and Aim: Population‐based studies on post‐colonoscopy colorectal cancer (CRC) from Asia are sparse. We aimed to determine the characteristics and predictive factors and survival of post‐colonoscopy CRC in Hong Kong. Methods: This is a territory‐wide retrospective cohort study. Patients aged ≥ 40 years with colonoscopies performed between 2005 and 2013 without history of CRCs, inflammatory bowel disease, and prior colectomy were included. Post‐colonoscopy colorectal cancer for an interval of 3 years (PCCRC‐3y) was defined as CRC diagnosed between 6 and 36 months after index colonoscopy, whereas CRC diagnosed within 6 months of index colonoscopy was regarded as "detected CRC." We used multivariable logistic regression to derive adjusted odds ratio (aOR) of PCCRC‐3y and Cox model for adjusted hazard ratio (aHR) of cancer‐specific mortality after CRC diagnosis. Results: Of the 197 902 eligible patients, 10 005 (92.1%) were detected CRC and 854 (7.9%) PCCRC‐3y. The median age at PCCRC‐3y diagnosis was 75.9 years (interquartile range: 65.5–83.8)—a delay of 1.2 years (interquartile range: 0.8–1.9) from index colonoscopy—and 60.1% were male. Predictive factors for PCCRC‐3y included older age (aOR: 1.07), male sex (aOR: 1.45), history of colonic polyps (aOR: 1.31), polypectomy/biopsy at index colonoscopy (aOR: 3.97), surgical endoscopists (aOR: 1.53), and a higher center annual endoscopy volume. Independent predictive factors for cancer‐specific mortality after CRC diagnosis included PCCRC‐3y (aHR: 1.32), proximal cancer location (aHR: 1.80), and certain patient factors. Conclusion: The PCCRC‐3y rate was 7.9% in Hong Kong, with a high proportion (> 80%) of distal cancers and a higher cancer‐specific mortality compared with detected CRC.